First record of Sigmodon minor (Rodentia) in the early Blancan of central Mexico: Asymmetrical dispersal from the Great Plains and paleoecology inferences - Adolfo Pacheco-Castro; Oscar Carranza-Castañeda; Xiaoming Wang (PLoS ONE, 2026)
In this study, we report the first occurrence of Sigmodon minor (Cricetidae, Rodentia) in Mexico, from the early Blancan of the Pliocene in the San Miguel de Allende Basin, Guanajuato. This record represents an early and rapid dispersal of these rodents from the Great Plains to lower latitudes, likely driven by climatic fluctuations during the late Neogene that favored the expansion of grassland biomes. The fossils described here are among the most complete for this species, including well-preserved mandibles and maxillary elements, found in association with megafauna and supported by radiometric age data. Detailed comparisons of molar dental occlusal structures and evolutionary stages with other contemporary records from North America were conducted. Palaeoecological inferences based on body size suggest a predominance of open grassland ecosystems interspersed with wetland niches, reflecting a complex mosaic of environmental conditions.